FAP-specific PET signaling shows a moderately positive correlation with relative CBV and no correlation with ADC in 13 IDH wildtype glioblastomas. Issue 127 (June 2020) - Röhrich, Manuel; Floca, Ralf; Loi, Lisa; Adeberg, Sebastian; Windisch, Paul; Giesel, Frederik L.; Kratochwil, Clemens; Flechsig, Paul; Rathke, Hendrik; Lindner, Thomas; Loktev, Anastasia; Schlemmer, Heinz Peter; et al.
Highlights: FAP-specific PET signaling in glioblastomas shows a moderately positive correlation with rCBV. FAP-specific PET signaling in glioblastomas shows no correlation with ADC. FAP-specific PET/CT is an independent novel imaging modality for glioblastomas. Abstract: Objectives: Targeting Fibroblast Activation Protein (FAP) is a new approach for glioblastoma imaging. In a recent pilot study glioblastomas showed elevated tracer uptake with high intratumoral heterogeneity in projection on the corresponding T2w/FLAIR and contrast enhanced MRI lesions. In this study, we correlated FAP-specific signaling with apparent diffusion coefficient (ADC) and relative cerebral blood volume (rCBV) signals in MRI to further characterize the significance of FAP uptake. Methods: Clinical PET/CT scans of 13 glioblastoma patients were performed post i. v. administration of 68 Ga-labelled-FAP-specific tracer molecules. PET- and corresponding MRI-scans were co-registrated. 3d volumetric segmentations were performed of T2w/FLAIR lesions and contrast enhancing lesions within co-registrated MRI slides. Signal intensity values of FAP-specific PET signaling, ADC and rCBV were analyzed for their pixel wise correlation in each patient. Pooled estimates of the correlation coefficients were calculated by using the Fisher z-transformation. Results: FAP-specific PET signals showed a moderately positive correlation with rCBV values which is more pronounced within the T2w/FLAIR lesion (pooled correlation 0, 229) than in the contrast enhancing tumor region (pooled correlation 0.09). FAP-specific PET signals showed no correlation with ADC values. Conclusions: The moderately positive correlation of FAP-specific signals with rCBV values in MRI indicates that FAP-signaling is not independent from perfusion, but also does not only reflect intratumoral perfusion differences. The missing correlation of FAP-specific signals with ADC indicates that FAP-specific imaging does not reflect cell density, but the spot-like expression of FAP in glioblastomas. The clinical value of FAP-specific imaging needs further investigation.